Incomplete removal of the RNA primer for minus-strand DNA synthesis by human immunodeficiency virus type 1 reverse transcriptase. - Pullen, K A (1992)
A synthetic RNA oligonucleotide (15-mer) corresponding to the 3' end of the lysine tRNA primer was hybridized to single-stranded DNA containing the human immunodeficiency virus type 1 (HIV-1) primer-binding site and extended with a DNA polymerase. The resulting structures were used to study primer removal by the RNase H activity of HIV-1 reverse transcriptase. The initial cleavage event removes the RNA primer as a 14-mer and leaves a single ribonucleotide A residue bound to the 5' end of the DNA strand. This result explains the observation by several groups that HIV-1 circle junctions contain 4 bp that are not present in the integrated provirus instead of the predicted 3 bp. Subsequent cleavage events occur at other sites internal to the RNA molecule, and the ribonucleotide A residue on the end of the DNA strand is ultimately removed. Therefore, the biologically relevant cleavage that produces the 14-mer reflects the kinetics of the reaction as well as a specificity for nucleic acid sequence. When the RNA oligonucleotide alone was hybridized to the primer-binding site and tested as a substrate for HIV-1 RNase H, the cleavage pattern near the 3' end of the RNA was altered.